THYROID METASTASIS OF A SQUAMOUS CELL CARCINOMA OF THE TONGUE - A RARE CASE REPORT - Gergana Tosheva; Mira Siderova; Elitsa Encheva; Doroteya Malinova (Peytchinski Publishing, 2021)
Introduction: We present a patient with carcinoma of the tongue with а lymph node and thyroid metastasеs. The squamous cell cancer of the tongue's 5-year survival rate has not been improved in the last three decades. Most common sites of metastases are the locoregional lymph nodes, followed by distant pulmonary, liver, bone and skin metastasеs. Only ten cases of metastases to the thyroid gland are reported in the literature. Case report: A 79-year old man presented to the University Hospital in Varna, Bulgaria. Two months before admission, he noticed swelling of the tongue and progressive weight loss. The inspection of the oral cavity revealed a lesion on the left margin of the tongue. A biopsy was performed with a histological result of differentiated squamous cell carcinoma of the tongue. A computed tomography scan of the head and neck region discovered a lesion in the right thyroid lobe. 18-fluoro-2-deoxy-glucose-positron emission tomography imaging showed a metabolically active tumor of the tongue with hypermetabolic metastatic cervical lymph nodes and a zone with abnormally elevated fixation of 18F-FDG in the central part of the soft palate. The described thyroid nodule did not have an increased tracer uptake. It was cytologically assessed after fine-needle aspiration biopsy (FNAB) as a metastasis from squamous cell carcinoma of the tongue. Conclusions: Distant metastases from tongue cancer to the thyroid gland are extremely rare and mostly occur in the advanced stages of malignancy.